Farnesoid X Receptor Agonist as a new treatment option for Non-Alcoholic Fatty Liver disease: A Review - Sukhpreet Singh; Kusum K Kharbanda (Archives of Hepatitis Research - Peertechz Publications, 2017)
Background: Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of fatty liver, characterized by the accumulation of fat in the hepatocytes in the absence of alcohol consumption. The spectrum of this disease ranges from steatosis to hepatitis and fi nally cirrhosis and hepatocellular  carcinoma. NAFLD pathogenesis is not completely understood but various risk factors like obesity, insulin resistance, and metabolic syndromes have been identifi ed. With the rapid increase in obesity and  diabetes during the past decade, the incidence of NAFLD is on the rise and is predicted to become the most common indication for liver transplantation in the future. Context of the study: The treatment option for NAFLD is limited and mainly focuses on risk factor modifi  cation like dietary changes and exercise. A major shortcoming of this approach is the lack of adherence and non-compliance over time. Other therapeutic options are available but are limited in number and have questionable effi cacy and safety profi les. Thus, new target-oriented therapies are needed. Results: One such option is using agonists of the farnesoid X receptor (FXR) which are nuclear receptors abundantly expressed in the liver and shown to play a key role in various metabolic pathways such as bile acid, cholesterol, lipid and glucose metabolism. Main focus and conclusions: In this review, we mainly discuss the role of FXR in the pathophysiology of NAFLD and how it can be a useful treatment target for such patients.